Diagnóstico poblacional del lobo del páramo (Lycalopex culpaeus) para el aprovechamiento turístico en el Parque Nacional Llanganates. - Lema Iza, Juan Gabriel (2018)
The purpose of this research is to determine the feasibility of taking advantage of the presence of the andean wolf as a tourist resource. For which, the distribution and the presence of this animal and other species of big mammals (bear and deer) was analized in ecological recovery zone II and III on the páramos of Llanganates National Park of the parish San Miguel, Canton Salcedo, of the Cotopaxi Province in the period October 2017 - February 2018. Through the implementation of linear transects at random, continuous monitoring through frequent routes, which allowed registering the species directly (observation) and indirectly (traces of feces and traces). Resulting in the sighting of two páramo wolves, one antelope bear and 33 white-tailed bandages, which are distributed throughout the study area; however, a frequent encounter with the wolf is not feasible. With the records obtained from the páramo wolf and other species of large mammals, a distribution map was drawn up where the exact place of the record made in the study area was located. Through the distribution map the user has the possibility of knowing the paths traveled by the species of large mammals, mainly the wolf of páramo, besides the maps and the analysis of the results allowed to establish the infeasibility of using the sighting of wolves of páramo as a tourist resource. Since it is very difficult to find it and there is no predisposition of the surrounding communities to work on similar topics to tourism based on biodiversity. However, the presence of white-tailed deer is notorious, since in most of the trips made was detected by traces (footprints, feces) and direct observation, for this reason it is recommended to conduct a specific study about this species to use it as a resource for tourist use.